Health, Work, and Family Strain – Psychosocial Experiences at the Early Stages of Long-Term Sickness Absence - Standal, Martin I.; Foldal, Vegard S.; Hagen, Roger; Aasdahl, Lene; Johnsen, Roar; Fors, Egil A.; Solbjør, Marit (Frontiers in Psychology, 2021)
Background: Knowledge about the psychosocial experiences of sick-listed workers in the first months of sick leave is sparse even though early interventions are recommended. The aim of this study was to explore psychosocial experiences of being on sick leave and thoughts about returning to work after 8-12 weeks of sickness absence. Methods: Sixteen individuals at 9-13 weeks of sick leave participated in semi-structured individual interviews. Data was analysed through Giorgi’s descriptive phenomenological method. Results: Three themes emerged: (1) energy depleted, (2) losing normal life, (3) searching for a solution. A combination of health, work and family challenges contributed to being drained of energy, which affected both work- and non-work roles. Being on sick leave led to a loss of social arenas and their identity as a contributing member of society. Participants required assistance to find solutions towards returning to work. Conclusions: Even in this early stage of long-term sick leave, sick listed workers faced complex challenges in multiple domains. Continuing sick leave was experienced as necessary but may challenge personal identity and social life. Those not finding solutions may benefit from additional early follow-up that examine work-related, social and personal factors that influence return to work.